Organophosphate esters flame retardants in the indoor environment - Vykoukalová, Martina; Venier, Marta; Vojta, Šimon; Melymuk, Lisa; Bečanová, Jitka; Romanak, Kevin; Prokeš, Roman; Okeme, Joseph O; Saini, Amandeep; Diamond, Miriam L; Klánová, Jana (Environment international, 2017)
Concentrations of 13 organophosphate ester flame retardants (OPEs) were measured in air, dust and window wipes from 63 homes in Canada, the Czech Republic and the United States in the spring and summer of 2013 to look for abundances, differences among regions, and partitioning behavior. In general, we observed the highest concentrations for halogenated OPEs, particularly TCEP, TCIPP and TDCIPP, and also non-halogenated TPHP. Differences between regions strongly depended on the matrix. The concentrations of OPEs in dust were significantly higher in the US than in Canada (CAN) and Czech Republic (CZ). CZ had the highest concentrations in window film and CAN in air. ΣOPE concentrations were 2-3 and 1-2 orders of magnitude greater than ΣBFRs in air, and dust and window films, respectively. We found a significant relationship between the concentrations in dust and air, and between the concentrations in window film and air for OPEs with log KOA values <12, suggesting that equilibrium was reached for these compounds but not for those with log KOA>12. This hypothesis was confirmed by a large discrepancy between values predicted using a partitioning model and the measured values for OPEs with log KOA values >12.
Keywords: prach; Dust; retardanty hoření; Organophosphates; Environmental Monitoring; Flame Retardants; Organophosphate esters (OPEs); Air Pollutants; Indoor Environment; Window Film; látky znečišťující vzduch; Air Concentration; monitorování životního prostředí; Indiana; organofosfáty; roční období; Esters; Ontario; Seasons; Czech Republic; Air Pollution, Indoor; Human Exposure; Indoor Dust; Česká republika; znečištění vzduchu ve vnitřním prostředí; estery